Histologic Features of Postnatal Development of Immune System Organs in the Sprague-Dawley Rat. (August 2015) - Parker, George A.; Picut, Catherine A.; Swanson, Cynthia; Toot, Jonathan D.
The immune system of the rat undergoes substantial functional and morphological development during the postnatal period. Some aspects of this development are genetically predetermined, while other aspects depend on environmental influences. Detailed information on postnatal development is important in the interpretation of histopathologic findings in juvenile toxicology and pubertal assay studies, as well as other studies conducted in juvenile rats. Studies were conducted to provide detailed characterization of histologic features of the major functional compartments of immune system organs in male and female Sprague-Dawley rats at weekly intervals from the day of birth through postnatal day (PND) 42. Maturation of the individual immune system organs occurred across a range of ages, with histologic maturation of T-cell-related compartments typically occurring prior to maturation of B-cell-related compartments. The sequence of histologic maturation was bone marrow and thymus on PND 14, mesenteric lymph node on PND 21, Peyer's patches and bronchus-associated lymphoid tissue on PND 28, mandibular lymph node, nasopharynx-associated lymphoid tissue, and diffuse mucosal mononuclear cell population of small intestine on PND 35, and spleen on PND 42. An estimation of functional maturation can be made based on the morphological indications of maturity of each compartment of immune system organs, but histologic indications of maturity do not confirm functional immunocompetence.